Designing a drinking water treatment experiment as a virtual lab to support engineering education during the COVID-19 outbreak. Issue 1 (31st December 2022) - Méndez Ruiz, J. I.; Valverde Armas, P. E.
Abstract: The design and deployment of a conventional water treatment experiment, the Jar Test, are presented in a virtual format. It used a low-cost online platform to reproduce the experimental steps and the actual lab setting to empower students with experiential skills. Skills like experimentation, instrumentation, learning from failure, and communication for their professional success. These skills are evaluated in the accreditation criteria for engineering programs of the Accreditation Board for Engineering and Technology. This virtual experience provided one-hundred and sixty-three civil engineering students with the knowledge to perform experimentation at an engineering level, from water sampling campaigns to performing the Jar Test experiment and measuring physicochemical quantities to draw technical conclusions. According to students' perceptions, the simulation strengthened their capacity for conducting experiments and data collection-processing using virtualized lab instruments. It also consolidated theoretical knowledge to report conclusions according to research findings and enhanced their confidence to perform in-person experiments based on the revised virtual procedure. The results from this study demonstrate that virtual tools could be deployed as a powerful supplement to deliver the practical syllabus when limitations of face-to-face interaction occur. It can also be a blended educational approach since the computer-assisted simulation provides the necessary pre-knowledge that maximizes learning during in-person experimentation.